Integration of transcriptomics and metabolomics data specifies the metabolic response of Chlamydomonas to rapamycin treatment - Kleessen, Sabrina; Irgang, Susann; Klie, Sebastian; Giavalisco, Patrick; Nikoloski, Zoran (The Plant journal : for cell and molecular biology, 2015)
Flux phenotypes predicted by constraint‐based methods can be refined by the inclusion of heterogeneous data. While recent advances facilitate the integration of transcriptomics and proteomics data, purely stoichiometry‐based approaches for the prediction of flux phenotypes by considering metabolomics data are lacking. Here we propose a constraint‐based method, termed TREM‐Flux, for integrating time‐resolved metabolomics and transcriptomics data. We demonstrate the applicability of TREM‐Flux in the dissection of the metabolic response of Chlamydomonas reinhardtii to rapamycin treatment by integrating the expression levels of 982 genes and the content of 45 metabolites obtained from two growth conditions. The findings pinpoint cysteine and methionine metabolism to be most affected by the rapamycin treatment. Our study shows that the integration of time‐resolved unlabeled metabolomics data in addition to transcriptomics data can specify the metabolic pathways involved in the system's response to a studied treatment.